1989
DOI: 10.1016/0304-3959(89)90047-x
|View full text |Cite
|
Sign up to set email alerts
|

Noxious stimuli produce prolonged changes in the CA1 region of the rat hippocampus

Abstract: Limbic structures including the hippocampus are thought to be involved in pain though not much is known of their neuronal responses to noxious stimuli. In this report we show that a prolonged and substantial depression of the dorsal hippocampal CA1 pyramidal cell population spike is produced by a brief but intense noxious stimulus applied to the tail of lightly anaesthetized rats. This depression is temperature-dependent and habituates to subsequent noxious stimuli applied more than 1 h later. Further, the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Overall, all of these four studies provide converging evidence that painful stimulation can indeed elicit electrophysiological changes in the septum and HF, the response pattern of which partially relies on the cholinergic inputs. Furthermore, this depression of neuronal transmission was found to be dependent on the hippocampal EEG state of the animal [150] . To further characterize this phenomenon, Khanna and Sinclair [75] reported that: (1) sal hippocampal CA1 pyramidal cell responses to a persistent (formalin pain) versus an acute nociceptive stimulus [56] .…”
Section: Influences Of Cholinergic Input On Pain-evoked Responsesmentioning
confidence: 91%
“…Overall, all of these four studies provide converging evidence that painful stimulation can indeed elicit electrophysiological changes in the septum and HF, the response pattern of which partially relies on the cholinergic inputs. Furthermore, this depression of neuronal transmission was found to be dependent on the hippocampal EEG state of the animal [150] . To further characterize this phenomenon, Khanna and Sinclair [75] reported that: (1) sal hippocampal CA1 pyramidal cell responses to a persistent (formalin pain) versus an acute nociceptive stimulus [56] .…”
Section: Influences Of Cholinergic Input On Pain-evoked Responsesmentioning
confidence: 91%
“…For example, Sacchetti et al demonstrated that shock, alone, did not affect baseline excitability in the hippocampus, in vitro, either soon after shock delivery or 7 days later. Numerous other studies on the hippocampus, in vitro and in vivo, have shown that stress or corticosterone can block LTP without increasing baseline excitability (Foy et al, 1987;Khanna and Sinclair, 1989;Diamond et al, 1990;Khanna and Sinclair, 1992;Shors and Dryver, 1994;Diamond et al, 1994;Hesen and Joels, 1996a;Garcia et al, 1997;Xu et al, 1997;Khanna, 1997;Shors et al, 1997b;Bramham et al, 1998;Garcia et al, 1998b;Mesches et al, 1999;Diamond et al, 1999a;Alfarez et al, 2002;Yamada et al, 2003;Joels et al, 2003;Kim et al, 2005). This issue was revisited recently by Kim et al, (2005), who noted that stress blocked the induction of LTP, but did not increase baseline synaptic transmission in CA1, as indicated by an absence of stress effects on inputoutput (I/O) functions (p. 1538).…”
Section: Does Stress Generate An Endogenous Form Of Ltp?mentioning
confidence: 99%
“…Therefore, the hippocampus was investigated since it is replete with α 2 -adrenergic receptors (Scheinin et al, 1994) that inhibit NE release (Kiss et al, 1995). The hippocampus is also involved in processing painful stimuli and regulating mood states (Delgado, 1954;Dutar et al, 1985;Khanna and Sinclair, 1989;McEwen, 2001;McKenna and Melzack, 1992). Furthermore, tricyclic antidepressant drugs (desipramine, amitriptyline, zimelidine) elicit neuroplastic changes in the regulation of NE release from the hippocampus following i.p.…”
Section: Introductionmentioning
confidence: 99%